Clustering of adverse and positive childhood experiences: The nature and correlates of risk and protective factors. (December 2022) - Craig, Jessica M.; Wolff, Kevin T.; Baglivio, Michael T.
Abstract: Background: Despite the increased attention paid to the separate effects of cumulative stress and protection on offending, the extent to which distinct clusters of risk and protective factors exist and have unique effects on justice-related outcomes is under-studied. Objective: The current study examines for unique clustering of Adverse Childhood Experiences (ACE) and Positive Childhood Experiences (PCE) and the extent to which they predict juvenile recidivism. Participants and setting: The sample consists of a cohort of youth adjudicated delinquent in Florida who received a community-based sanction. Methods: The study first utilized latent-class analysis to identify distinct classes based upon the youths' ACE and PCE exposures. Next, two sets of regression models were estimated; the first investigated correlates of class membership and the second assessed whether class membership predicted recidivism. Results: Seven distinct classes of ACE/PCE clusters were found, composing 9.9 % to 20.5 % of the sample each. Relative to the class with low ACE and low PCE, those with low ACEs and high PCE evidenced 27.5 % lower rearrest rates, as did the Moderate Risk/Moderate Protection group. Conclusions: Not only do distinct groupings of ACE and PCE exposures exist, but these groups have different likelihoods of future offending, where a youth's cumulative protection appears to be more important than their risk level. This has important policy implications as it offers further support for the use of strength-based treatment approaches. Highlights: This study identified unique groupings of cumulative risk and protective factors. Group membership was predictive of likelihood of reoffending. The groups' overall level of protection, but not risk, predicted reoffending.